Regulatory Preconditions for the Deployment of Bioenergy With Carbon Capture and Storage in Europe - Nehler, Therese; Fridahl, Mathias (Frontiers in Climate, 2022)
Paris-compatible climate scenarios often consider bioenergy with carbon capture and storage (BECCS) as an important technology for carbon dioxide removal (CDR). Although the main barrier to BECCS deployment is often associated with lack of economic policy incentives, unfavourable regulations can also impede investments. Over the past decade, the regulatory conditions by the UN and on EU level have developed to be more permissive towards BECCS. For instance, CDR accounting guidelines have been developed by the UN, and the EU CCS Directive regulates responsibilities regarding storage of CO2. However, several existing regulations still maintain deployment hurdles. Taking a European viewpoint, this Perspectives article takes stock of recent regulatory developments and provides a discussion on legal acts that need to be reformed to facilitate BECCS deployment. Although the European trend is characterized by developing a regulatory regime that is more supportive of BECCS, we identify three areas for further improvement: 1) allow EU Member States to use negative emissions from BECCS to comply with their obligations under the legislative pillars that underpin the EU’s climate objectives: 2) amend the CCS Directive to exempt physical leakage of biogenic CO2, attributable to sustainably sourced biomass, from the requirement to surrender emission allowances in the EU ETS; and 3) push to erase the last few barriers provided by multilateral regimes, such as to clarify whether BECCS is covered by the geoengineering moratorium maintained by the UN Convention on Biological Diversity. These proposed reforms would further improve the regulatory preconditions for BECCS deployment in the EU.